2007
DOI: 10.1002/jcb.21229
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐loaded HepG2 spheroids exhibit enhanced protection from Pro‐oxidant and cytokine induced damage

Abstract: The mechanisms by which steatosis renders hepatocytes susceptible to damage in non-alcoholic steatohepatitis (NASH) are unclear although fat accumulation is believed to increase hepatocyte susceptibility to inflammatory cytokines and oxidative stress. We therefore investigated the susceptibility of steatotic, hepatocyte-derived cells to TNFalpha and the pro-oxidant, t-butylhydroperoxide (TBH). HepG2 spheroids rendered steatotic by fat-loading with 0.15 mM oleic or palmitic acid for 48 h and treated with TNFalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This aggravation of liver injury was probably caused by increasing intracellular levels of free fatty acids, oxidative stress, inflammation, and fibrosis (Yamaguchi et al, 2007). The role of intracellular lipid accumulation as cellular protection mechanism for oxidative stress was further supported in an in vitro model of fat-loaded (palmitic or oleic acid) HepG2 spheroids, which, when challenged with pro-oxidants, were found to display lower levels of cytotoxicity and increased antioxidant activity than nonsteatotic controls (Damelin et al, 2007).…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 94%
See 1 more Smart Citation
“…This aggravation of liver injury was probably caused by increasing intracellular levels of free fatty acids, oxidative stress, inflammation, and fibrosis (Yamaguchi et al, 2007). The role of intracellular lipid accumulation as cellular protection mechanism for oxidative stress was further supported in an in vitro model of fat-loaded (palmitic or oleic acid) HepG2 spheroids, which, when challenged with pro-oxidants, were found to display lower levels of cytotoxicity and increased antioxidant activity than nonsteatotic controls (Damelin et al, 2007).…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 94%
“…It is noteworthy that observations that monounsaturated FAs also had protective effects in hepatic steatosis, although they had a stimulating effect on triglyceride synthesis, led to introduction of an interesting hypothesis stating that monounsaturated FAs may prevent palmitate-induced lipoapoptosis by channeling excess saturated FAs toward triglyceride synthesis and lipid storage away from activation of lipotoxic cell death via metabolism of palmitate to ceramide classes (Listenberger et al, 2003;Damelin et al, 2007). Therefore, intracellular triglyceride storage in the liver may protect, at least in part, from oxidative stress or lipotoxins.…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 99%
“…In support of this, Diehl and colleagues demonstrated that inhibition of hepatocyte triglyceride synthesis and steatosis increased liver injury and fibrosis in obese mice with NASH [38]. Moreover, oleate-or palmitate-loaded HepG2 spheroids (hepatocyte-derived cells) were less susceptible to cytokine or peroxide induced cell death [39]. Taken together, these results are intriguing because they indicate that steatosis may not be the "first-hit" or a pre-requisite in the pathogenesis of ASH or NASH.…”
Section: Introductionmentioning
confidence: 90%
“…Oleic acid-treated HepG2 spheroids have also been proven useful in vitro tools for studying hepatic steatosis. These spheroids were surprisingly less susceptible to cytokine and pro-oxidant damage via an adaptive mechanism dependent on adenosine monophosphate-activated protein kinase activity [239]. Additionally, a spheroid model of primary hepatocytes from male Sprague Dawley rats shows higher intracellular glycogen content, glucose consumption, and gluconeogenesis, and a more in vivo -like sensitivity to insulin and glucagon in comparison with monolayer cultures.…”
Section: Models In Nafld Researchmentioning
confidence: 99%